Analysis of Aleutian disease virus infection in vitro and in vivo: demonstration of Aleutian disease virus DNA in tissues of infected mink. - Bloom, M E (1985)
Aleutian disease virus (ADV) infection was analyzed in vivo and in vitro to compare virus replication in cell culture and in mink. Initial experiments compared cultures of Crandell feline kidney (CRFK) cells infected with the avirulent ADV-G strain or the highly virulent Utah I ADV. The number of ADV-infected cells was estimated by calculating the percentage of cells displaying ADV antigen by immunofluorescence (IFA), and several parameters of infection were determined. Infected cells contained large quantities of viral DNA (more than 10(5) genomes per infected cell) as estimated by dot-blot DNA-DNA hybridization, and much of the viral DNA, when analyzed by Southern blot hybridization, was found to be of a 4.8-kilobase-pair duplex monomeric replicative form (DM DNA). Furthermore, the cultures contained 7 to 67 fluorescence-forming units (FFU) per infected cell, and the ADV genome per FFU ratio ranged between 2 X 10(3) and 164 X 10(3). Finally, the pattern of viral antigen detected by IFA was characteristically nuclear, although cytoplasmic fluorescence was often found in the same cells. Because no difference was noted between the two virus strains when cultures containing similar numbers of infected cells were compared, it seemed that both viruses behaved similarly in infected cell culture. These data were used as a basis for the analysis of infection of mink by virulent Utah I ADV. Ten days after infection, the highest levels of viral DNA were detected in spleen (373 genomes per cell), mesenteric lymph node (MLN; 750 genomes per cell), and liver (373 genomes per cell). In marked contrast to infected CRFK cells, the predominant species of ADV DNA in all tissues was single-stranded virion DNA; however, 4.8-kilobase-pair DM DNA was found in MLN and spleen. This observation suggested that MLN and spleen were sites of virus replication, but that the DNA found in liver reflected sequestration of virus produced elsewhere. A final set of experiments examined MLN taken from nine mink 10 days after Utah I ADV infection. All of the nodes contained ADV DNA (46 to 750 genomes per cell), and although single-stranded virion DNA was always the most abundant species, DM DNA was observed. All of the lymph nodes contained virus infectious for CRFK cells, but when the genome per FFU ratio was calculated, virus from the lymph nodes required almost 1,000 times more genomes to produce an FFU than did virus prepared from infected cell cultures.(ABSTRACT TRUNCATED AT 400 WORDS)